Sistem Prediksi Harga Kripto Dengan Metode Regresi - Muhammad Khoirul Anam; Deni Ahmad Jakaria (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Predicting crypto prices is a challenge because the crypto market is very volatile and unpredictable. In this work, we present a crypto price prediction system that uses the regression method to plot curves on a historical crypto price dataset. The system consists of several stages, including data collection, data pre-processing, model training, prediction, and evaluation. Model performance is evaluated by comparing the predictions made by the model with actual prices and calculating metrics such as mean absolute error or mean squared error. The system is expected to help in deciding to buy, sell or hold owned crypto assets and the system used uses the Python programming language which is one of the languages which has machine learning features for the implementation of artificial intelligence (AI).